2007
DOI: 10.1093/molbev/msm008
|View full text |Cite
|
Sign up to set email alerts
|

Der1-mediated Preprotein Import into the Periplastid Compartment of Chromalveolates?

Abstract: Phototrophic chromalveolates possess plastids surrounded by either 3 or 4 membranes, revealing their secondary endosymbiotic origin from an engulfed eukaryotic alga. In cryptophytes, a member of the chromalveolates, the organelle is embedded within a designated region of the host's rough endoplasmic reticulum (RER). Its eukaryotic compartments other than the plastid were reduced to the mere remains of its former cytosol, the periplastid compartment (PPC, PP space), and its nucleus, the nucleomorph, separated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
207
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(210 citation statements)
references
References 57 publications
2
207
1
Order By: Relevance
“…Besides such synthetic constructs, we screened all known endogenous PPC proteins (9,10,13,16,(29)(30)(31) for potential N-glycosylation sites using the program NetNGlyc 1.0. Interestingly, 23% of the 52 proteins possess potential N-glycosylation sites with high confidence predictions (++) within the mature, soluble protein (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides such synthetic constructs, we screened all known endogenous PPC proteins (9,10,13,16,(29)(30)(31) for potential N-glycosylation sites using the program NetNGlyc 1.0. Interestingly, 23% of the 52 proteins possess potential N-glycosylation sites with high confidence predictions (++) within the mature, soluble protein (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Signal peptide and transit peptide together are called bipartite targeting signal (BTS) and represent the classical targeting signature for preproteins destined to complex plastids. Recently, it was proposed that transport across the second plastid membrane of diatoms is mediated by an ER-associated degradation (ERAD)-derived translocation machinery, which was termed symbiontspecific ERAD-like machinery (SELMA) (12,13). Phylogenetic data together with molecular analyses suggest that during evolution, core components of the red algal ERAD-transport system were relocalized from the symbiont's ER to the second plastid membrane to mediate preprotein translocation (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This functional compatibility is also supported by 2 previous findings. The existence of an ER-associated degradation (ERAD)-like system for transporting preproteins across the second-from-theoutside of the 4 plastid-surrounding membranes in cryptophytes, heterokonts, and apicomplexans (39); and the capability of cryptophyte plastid-targeting peptide to deliver GFP into the plastids of the heterokont Phaeodactylum tricornutum (17). It appears that photosynthetic chromalveolates with secondary plastids use, at least in part, the protein-targeting signals for plastids of the red algal endosymbiont, which eventually became their own plastids.…”
Section: Functional Compatibility Of Bipartite Plastid-targeting Peptidementioning
confidence: 99%
“…What about the remaining membrane? Maier and colleagues have shown that translocation across the second outermost membrane (originally the plasma membrane of the algal endosymbiont) in red-type four-membrane plastids is mediated by a multiprotein complex dubbed SELMA [symbiont-specific endoplasmic reticulum (ER)-associated degradation-like machinery (68)(69)(70)(71)]. The evolution of SELMA appears to represent a singularity, an intricate complex cobbled together from a dozen or more proteins at least some of which originally functioned as part of the ER-associated degradation machinery in the red algal endosymbiont.…”
Section: Evolving a Complex Algamentioning
confidence: 99%